WA16 If my body is ill, who am i? pain relief through expression of whole self. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Woolf, Sarah
Abstract : Background: People rely on mobility and bodily capacity to define who they are. Little has been written about how bodily incapacity towards the end of life affects a person's self-concept. Expressive Movement Therapy (EMT) (also called Dance Movement Psychotherapy) enables people to use creative movement/gestures to express themselves physically, emotionally, socially and spiritually. This is the first known research about EMT in palliative care in the UK. Aim: To explore clients' experiences of EMT in a day hospice setting. Methods: A phenomenological/case study approach explored four clients' experiences of EMT in depth. Results: Participants used EMT to express how their ill bodies had become obstacles to defining who they are, causing a complex interaction between physical incapacity and emotional, social and spiritual pain. EMT released tension by enabling participants to grieve over these losses of self, and to re-integrate with their estranged bodies to express themselves as "me completely". Conclusion: This research provides a new understanding of the concept of 'total pain'. It links physical suffering to emotional, social, spiritual pain by showing that bodily incapacity prevents people from expressing their sense of whole self. EMT helps relieve this pain by offering people accessible, creative ways to reconnect with their ill, estranged bodies to express themselves as an integrated complete person. The community needs to adopt a holistic approach, which does not just focus on parts of the body, but recognises the importance of helping people sustain their self-narrative as a whole person in all dimensions of their lives.